Pengaruh Metode Karyawisata Terhadap Kreativitas Menggambar Anak di Taman Kanak-Kanak Bani Toifur Kabupaten Nganjuk - Pangastuti, Ratna; Qumillaila, Qumillaila (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2017)
Many kinds of learning methods for early age level in stimulate all aspects of its development. One of the methods is karyawisata method. With this method the children directly faced with concrete objects that corresponds to its development stage. In addition to play and and imagine, early children have extraordinary creativity level. In this study researchers want to know how much the influence of karyawisata method against the ability of creativity of early childhood (kindergarten) through activities such as drawing. Where the drawing included in the learning achievement indicator on the Fine motoric aspects. this study use the quantitative approach and analysis technique with product moment in order to measure the scale of